West meets Islam in contemporary world - Leadership perspective - Senam, Muhamad Rosdi; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Mohd Zaina, Rapiah (2015)
Abstract—Islam is a way of life than merely a religion that covers all facets of Muslim affairs and lifes. It provides the most comprehensive values, principles and guidance that are based on divine sources to all mankind in all spheres including leadership. Islamic leadership is all encompassing and holistic model of leadership that offers the tauhidic paradigm, spiritual and ethical (akhlaq) dimensions that are absent in the modern conventional leadership theories. Islamic leadership has a glorious history of great success from the era of the Prophet S.A.W. and the following caliphs that had conquered almost one third of the world territory during that time, as their leadership was paragon of excellence that followed to the spirits and teachings of the Qur’an and the Sunnah. As the modern civilisation designed by the West takes place, the modern leadership theories has been dominating the world and literature including those in the Muslim countries. However, it is clear that values and principles derived from Islam and the West are distinct, as the Islamic ones are based on divine, the non-Islamics are not indeed as there are based on human rational and judgement. Recent development in business organisations and literature have seen the tendency towards moral, ethical, even spiritual and positive form of leadership such as servant leadership, ethical leadership, authentic leadership and spiritual leadership that found its root in the Islamic model of leadership. This development has surfaced after series of serious ethical dilemma, corporate scandals and leadership crisis in the West. This paper aims to draw a comparative discussions and analysis between the modern conventional leadership theories with the Islamic leadership by highlighting the key dimensions that distinguish the two. It is suggested in this paper that the core dimensions of Islamic leadership are spiritual dimension, moral and ethical dimension and physical dimension which is also paralleled with the roles of khalifah of Allah on earth; relationship with Allah, relationship with human beings and relationship with the environment respectively.